Magnesium Supplements and Type 2 Diabetes Mellitus Control: A Narrative Review: Magnesium Supplements and T2DM (The Review of Diabetic Studies, 2024)
Background: Long-term hypomagnesaemia is associated with an increased risk of hyperinsulinemia and insulin resistance, and thus incidence of type 2 diabetes mellitus (T2DM). This study reviewed the available studies on magnesium (Mg) supplementation in patients with T2DM. Methods: Using databases (PubMed, Scopus, Medline via the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov), a literature was conducted for hypomagnesemia and its impact on T2DM and effect of Mg supplements on blood Mg concentrations and long-term associations with T2DM control or prognosis. Results: Observational studies and evidence from randomized clinical trials have demonstrated that low serum Mg concentrations in T2DM patients are associated with higher fasting blood glucose and glycated hemoglobin A1c, along with a higher incidence of diabetic retinopathy, nephropathy, neuropathy, and cardiovascular disease. In T2DM, evidence for the routine use of Mg supplements to improve disease control and prognosis is inconsistent and inconclusive. This is due to heterogeneity in Mg supplementation duration (4-16 weeks), variety in dosage (36.49-500 mg per day), and differences in the salt component of the tablets used in these studies. Conclusion: Mg supplementation is a simple and inexpensive modality for improving T2DM control. Therefore, the appropriate dose and duration of Mg supplementation should be determined.